Etiologic study of upper respiratory infections of household dogs - Mochizuki, M.(Kyoritsu Seiyaku Corp., Tokyo (Japan)); Yachi, A; Ohshima, T; Ohuchi, A; Ishida, T (Journal of Veterinary Medical Science, 2008)
Infectious tracheobronchitis (ITB), also known as the kennel cough, is a respiratory syndrome of dogs and usually appears to be contagious among dogs housed in groups. Etiologic agent of ITB is multiple and sometimes complex. In the present study, 68 household dogs showing clinical signs of respiratory infection were examined, and 20 dogs (29.4%) were found to be positive for either of following agents. Bordetella bronchiseptica (B.b.) was most frequently detected from nasal and oropharynx sites of 7 dogs (10.3%). Among the viruses examined, canine parainfluenza virus (CPIV) was detected with the highest frequency (7.4%). Other pathogens included in the order of frequency group 1 canine coronavirus (4.4%), canine adenovirus type 2 (2.9%), group 2 canine respiratory coronavirus (1.5%), and canine distemper virus (1.5%). Only 2 cases showed mixed infections. Neither influenza A virus nor canine bocavirus (minute virus of canines) was found in any dogs examined. These results indicate that both B.b. and CPIV are likely to be the principal etiologic agents of canine ITB in Japan, and they may be considered as the target for prophylaxis by vaccination.